An Analysis of Translation Techniques Used In The Encanto Film Subtitle - M, Nur Jannatul; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Translation of literary works including films is important because many films are in English in Indonesia and not many people can understand the language. Translating means communicating, that is conveying a message to others. In the translation process, it is necessary to follow the methods and techniques of translation. The researchers chose the Encanto as the object because the Encanto is an animation that could be presented by adults as well as children. In translating the film used technique of Molina and Albir which has a character where the techniques used are functional and unrelated to each other but are based on a certain context. After analyzing the data, there are 12 techniques were used by the translator to translate the dialog in the Encanto film, which contains 475 data, they are Borrowing (10 data), Established Equivalent (1 data), Generalization (1 data), Linguistic Amplification (13 data), Linguistic Compression (211 data), Literal Translation (155 data), Modulation (16 data), Particularization (3 data), Reduction (14 data), Substitution (10 data), Transposition (15 data), Variation (26 data).